Pengaruh Kompetensi Dosen, Motivasi Berprestasi, dan Penerapan Kurikulum terhadap Prestasi Belajar Mahasiswa (Suatu Kajian Studi Literatur Manajemen Pendidikan) - Ola Langoday, Thomas; Da Conceicao Ximenes, Helena; Perseveranda, M. E.; Man, Stanis; Hendrikus Temai Ledjab, Hedwigh (Dinasti Review, 2023)
Previous research and relevant research are very useful for a research or literature review of a scientific work both examining the influence between variables and other factors that also influence a variable itself. This article discusses a literature review of factors that have an impact on student learning achievement, namely lecturer competence, achievement motivation, and application of curriculum. this review intends to determine hypotheses that have an impact on each variable so that it can be useful for further research. The results of this writing make it clear if lecturer competence has a positive or crucial impact on student learning achievement; achievement motivation has a positive and crucial impact on student learning achievement; implementation of the curriculum has a positive and crucial impact on student learning achievement; lecturer competence, achievement motivation, and curriculum Implementation simultaneously have a positive and meaningful impact on student learning achievement.